Model Discovery Learning Berbantuan Media Video Edukasi dan Dampaknya terhadap Kemampuan Berpikir Kreatif Matematis - Septiana Septiana; Sri Yuliyanti; Ade Kurniawan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the effect of discovery learning model assisted by educational videos on students' mathematical creative thinking skills. This study uses a quantitative approach with a quasi-experimental type and a pretest-posttest nonequivalent control group design. The study was conducted at SMPN 13 Mataram on grade VII students in the 2025/2026 academic year. The research sample consisted of 84 students consisting of 42 students of grade VII D as the experimental class and 42 students of grade VII F as the control class. The sampling technique used purposive sampling. Data collection techniques were carried out through mathematical creative thinking ability tests and interviews. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, and independent sample t-test. The results showed that the average pre-test score of the experimental class was 47.31, increasing to 83.31 in the post-test, while the average pre-test score of the control class was 34.71, increasing to 70.57 in the post-test. The results of the hypothesis test on the post-test scores of the experimental and control classes showed a significance value of 0.000 <0.05, thus H₀ was rejected and H₁ was accepted. This indicates a significant difference between the mathematical creative thinking abilities of students who learned using the discovery learning model assisted by educational videos and those who learned using conventional learning. Thus, the discovery learning model assisted by educational videos significantly influenced the mathematical creative thinking abilities of seventh-grade students at SMPN 13 Mataram.